2012
DOI: 10.2319/032612-251.1
|View full text |Cite
|
Sign up to set email alerts
|

A PRISMA assessment of the reporting quality of systematic reviews in orthodontics

Abstract: AbstractObjectives:To assess the reporting quality of Cochrane and non-Cochrane systematic reviews (SR) in orthodontics and to compare the reporting quality (PRISMA score) with methodological quality (AMSTAR criteria).Materials and Methods:Systematic reviews (n  =  109) published between January 2000 and July 2011 in five leading orthodontic journals were identified and included. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 20 publications
6
61
0
4
Order By: Relevance
“…Reporting of orthodontic SRs in leading dentistry journals was found to be insufficient in their descriptions of registration of review protocols, reporting of funding sources, definition of summary measures, and detailed explanations of the analyzing methods and eligibility criteria. The reporting quality assessed using PRISMA guidelines was significantly better in orthodontic SRs published in the Cochrane Database of Systematic Reviews (Fleming, Seehra, & Polychronopoulou, 2013). The same result was found in another study that assessed the reporting quality of the SRs of stomatology published in specialist EBM journals (Li, Lv, & Su, 2011).…”
Section: Implications For Nurses Researchers and Journal Editorssupporting
confidence: 73%
“…Reporting of orthodontic SRs in leading dentistry journals was found to be insufficient in their descriptions of registration of review protocols, reporting of funding sources, definition of summary measures, and detailed explanations of the analyzing methods and eligibility criteria. The reporting quality assessed using PRISMA guidelines was significantly better in orthodontic SRs published in the Cochrane Database of Systematic Reviews (Fleming, Seehra, & Polychronopoulou, 2013). The same result was found in another study that assessed the reporting quality of the SRs of stomatology published in specialist EBM journals (Li, Lv, & Su, 2011).…”
Section: Implications For Nurses Researchers and Journal Editorssupporting
confidence: 73%
“…However, an established threshold for assigning descriptive quality or an overall quality score has not yet been established; therefore, a Bhigher^AMSTAR score, rather than a Blower^AMSTAR score, may help to reveal methodologically sound systematic reviews. Conversely, we identified some selected reviews, which showed that 20 % of included SR satisfied nine or more of the 11 AMSTAR criteria [17,18]. While it was out of the scope of this review to explore reasons for differences in methodological quality of SR across dental disciplines, the present results may serve as reference for further methodological development of SR published in these fields.…”
Section: Discussionmentioning
confidence: 87%
“…The three least common topics were restorative dentistry (n=15; 2.3 %), pain (n=11; 1.7 %), and other unclassified studies (n=25; 3.9 %). Although the median number of studies per SR was [15][16][17][18][19][20][21][22][23][24][25][26][27][28], the majority (70.2 %, n=450) included fewer than 24 studies in their review, while 2.0 % (n=13) included more than 100 studies. Most studies failed to describe study characteristics (88.2 %, n = 567), with terms such as Badults^(6.5 %, n = 42) or Bpaediatrics^(5.3 %, n = 34) populations used sparingly among the studies.…”
Section: Description Of Studies Meeting Our Inclusion Criteriamentioning
confidence: 99%
“…In a study of 109 systematic reviews published in major orthodontic journals, 26 were published in the Cochrane Database of Systematic Reviews. In all, 21% of the selected reviews satisfied 9 or more of the 11 AMSTAR criteria [64,65]. However, to our best knowledge, no methodological survey concerned specifically pediatric oral health.…”
Section: Discussionmentioning
confidence: 99%